Enhancing the Implementation of Sustainable Development in Nigeria through Legal Strategies - Jerome, Orji Uchenna (Consilience, 2012)
Despite an abundance of resources, attempts to reduce poverty and promote sustainable development have not become a reality in Nigeria. This article suggests legal routes for supporting Nigerian sustainable development, including the establishment of a constitutional right to sustainable development alongside intergenerational rights; public interest litigation; and the recognition of the public trust doctrine and budget analysis.